In Vitro Germination of Dumbaya Seeds (Momordica cochinchinensis (Lour.) Spreng: A Unique Medicinal Plant of Gorontalo - Devi Bunga Pagalla; Jusna Ahmad; Miftahul F. Adudu; Adilah Nidaulhasanah; Fitria H.Ys. Adju; Evita Moni Damayanti (Jurnal Biologi Tropis, 2023)
"Dumbaya (Momordica cochinchinensis (Lour.) Spreng) is one of the plant species believed by the Gorontalo community to be a traditional remedy for various ailments such as inflammation, liver disorders, spleen issues, hemorrhoids, bruising, and infected wounds. Currently, the dumbaya plant is difficult to find and is even considered nearly extinct by the Gorontalo community. This is due to the challenging conventional cultivation of dumbaya plants from seeds. Dumbaya seeds have a hard, stone-like texture, making germination in the wild difficult and requiring special treatment. Regeneration of dumbaya can be achieved through tissue culture techniques, replacing the conventional cultivation system.Through tissue culture, dumbaya seeds are grown in specialized planting media and controlled environments. Based on observations, the propagation of dumbaya plants using in vitro culture techniques has proven successful and effective as a solution for propagating dumbaya seedlings. Dumbaya seeds begin to germinate two weeks after planting (2 WAP). The grown dumbaya seedlings can then be used as explants for further dumbaya propagation by inducing callus formation."